Sodno varstvo zoper prostorske izvedbene akte - Pucelj Vidović, Tanja (Podjetje in delo, 2020)
The article focuses on the legal protection against provisions of spatial planning ("zoning") acts, as regulated in the Spatial Planning Act (ZUreP-2). As it is always the case, also this novelty triggers many dilemmas. This article therefore includes a discussion on whether it is constitutionally permissible to determine the jurisdiction of the Administrative Court and discusses the issue of whether there is an (un)satisfactory division of competences between the Administrative and the Constitutional Court. It includes a short discussion on standing and the scope of judicial control. It presents the consequences of such lawsuit and discusses the distinction between the suspension of the implementation and suspension of the enforcement of the zoning act. It argues that the pleas that can lead to a successful action should be regulated at least partly differently to a lawsuit against an individual act. Concerns are expressed about the possibility of challenging the provisions of the DPN Regulation and certain shortcomings of the procedure are highlighted. The author expresses an opinion that, in such disputes, the court is not allowed to decide in the dispute of full jurisdiction. The author also holds the opinion that a requirement for the court to determine the manner in which its judgment is to be enforced is contrary to the purpose of spatial planning and the principle of separation of powers, it disrupts the original competence of the municipality, and should therefore be abandoned or changed. The author believes that Article 58 needs to be improved, but advocates that the solution it introduces should as a principle be preserved.